2022
DOI: 10.1136/jitc-2022-004761
|View full text |Cite
|
Sign up to set email alerts
|

Nivolumab plus rucaparib for metastatic castration-resistant prostate cancer: results from the phase 2 CheckMate 9KD trial

Abstract: BackgroundCheckMate 9KD (NCT03338790) is a non-randomized, multicohort, phase 2 trial of nivolumab plus other anticancer treatments for metastatic castration-resistant prostate cancer (mCRPC). We report results from cohorts A1 and A2 of CheckMate 9KD, specifically evaluating nivolumab plus rucaparib.MethodsCheckMate 9KD enrolled adult patients with histologically confirmed mCRPC, ongoing androgen deprivation therapy, and an Eastern Cooperative Oncology Group performance status of 0–1. Cohort A1 included patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…PSA or radiologic progression occurred in 53% of patients [ 95 ]. CHeckMate 9KD [ 100 ] is a phase II trial assessing the safety and efficacy of nivolumab, a PD-1 inhibitor, in combination with rucaparib, docetaxel or enzalutamide in patients with mCRPC. Patients in cohort A received nivolumab 280 mg administered intravenously (IV) every 4 weeks with rucaparib 600 mg PO BID.…”
Section: Resultsmentioning
confidence: 99%
“…PSA or radiologic progression occurred in 53% of patients [ 95 ]. CHeckMate 9KD [ 100 ] is a phase II trial assessing the safety and efficacy of nivolumab, a PD-1 inhibitor, in combination with rucaparib, docetaxel or enzalutamide in patients with mCRPC. Patients in cohort A received nivolumab 280 mg administered intravenously (IV) every 4 weeks with rucaparib 600 mg PO BID.…”
Section: Resultsmentioning
confidence: 99%
“…While most studies are still ongoing, the trials reported to date have shown limited antitumor activity from the combination of PARPi with cediranib, 44 pembrolizumab, 51 or nivolumab 52 in mCRPC patients without detectable HRR alterations and for those with HRR defects it is unclear whether the combinations add any benefit to PARPi in monotherapy. The most promising results have been reported from trials investigating the combination of PARPi with ARSi, with several lines of work showing a close interplay between the AR pathway and the DDR machinery, supporting the synergistic effect of ARSi and PARPi.…”
Section: Parpi In Combinations For the Treatment Of Advanced Prostate...mentioning
confidence: 99%
“…PARP inhibitors have been shown to have synergistic effects with PD-1/PD-L1 or CTLA-4 blockade (126,127). A recent study of rucaparib in combination with nivolumab for mCRPC reported its results: regardless of previous chemotherapy (128), the CheckMate 9KD study showed significantly improved ORR and PSA response rates with combination therapy in the HRD+ cohort, particularly in patients with BRAC1/2 mutations; in terms of OS and rPFS, the median OS for the A2 cohort without chemotherapy was 20.2 months (95% CI 14.1-22.8 months) and the median rPFS was 8.1 months (95% CI 5.6-10.9 months). Regarding safety, common TRAEs observed following combination therapy were nausea, fatigue, anemia, and loss of appetite, with G3-G4 TRAEs occurring in half of the patients in both cohorts, and neutropenia warranting focus during treatment.…”
Section: Immunotherapy Combined With Parp Inhibitorsmentioning
confidence: 99%